Transperineal template prostate‐mapping biopsies: an evaluation of different protocols in the detection of clinically significant prostate cancer. (25th September 2015) - Valerio, Massimo; Anele, Chukwuemeka; Charman, Susan C.; van der Meulen, Jan; Freeman, Alex; Jameson, Charles; Singh, Paras B.; Emberton, Mark; Ahmed, Hashim U.
Abstract : Objectives: To determine whether modified transperineal template prostate‐mapping (TTPM) biopsy protocols, altering the template or the biopsy density, have sensitivity and negative predictive value (NPV) equal to full 5‐mm TTPM. Patients and Methods: Retrospective analysis of an institutional registry including treatment‐naïve men undergoing 5‐mm TTPM biopsy analysed in a 20‐zone fashion. The value of three modified strategies was assessed by comparing the information provided by selected zones against full 5‐mm TTPM. Strategy 1, did not consider the findings of anterior areas; strategies 2 and 3 simulated a reduced biopsy density by excluding intervening zones. A bootstrapping technique was used to calculate reliable estimates of sensitivity and NPV of these three strategies for the detection of clinically significant disease (maximum cancer core length ≥4 mm and/or Gleason score ≥3 + 4). Results: In all, 391 men with a median (interquartile range, IQR) age of 62 (58–67) years were included. The median (IQR) PSA level and PSA density were 6.9 (4.8–10) ng/mL and 0.17 (IQR 0.12–0.25) ng/mL/mL, respectively. A median (IQR) of 6 (2–9) cores out of 48 (33–63) taken per man were positive for prostate cancer. No cancer was detected in 67 men (17%), whilst low‐, intermediate‐ and high‐risk disease was identified in 78 (20%), 80 (21%), and 166 (42%), respectively. Strategy 1, 2 and 3 had sensitivities of 78% [95% confidence interval (CI) 73–84%], 85% (95% CI 80–90%) and 84% (95% CI 79–89%), respectively. The NPVs of the three strategies were 73% (95% CI 67–80%), 80% (95% CI 74–86%) and 79% (95% CI 72–84%), respectively. Conclusion: Altering the template or decreasing sampling density has a substantial negative impact on the ability of TTPM biopsy to exclude clinically significant disease. This should be considered when modified TTPM biopsy strategies are used to select men for tissue‐preserving approaches, and when modified TTPM are used to validate new diagnostic tests.